The World almanac and book of facts, 2015 - Janssen, Sarah 1982 (New York World Almanac Books, 2015)
A compendium of facts and statistics, ranging from the Obama presidency to the ebola outbreak, in a book that provides information for all the countries in the world and includes the top 10 news stories of the year.
Keywords: Almanacs, American; Statistics; United States -- Statistics